2015
DOI: 10.1177/1362361314566048
|View full text |Cite
|
Sign up to set email alerts
|

Onset of maternal psychiatric disorders after the birth of a child with autism spectrum disorder: A retrospective cohort study

Abstract: Background: Mothers of a child with autism spectrum disorder have more psychiatric disorders after the birth of their child. This might be because they have more psychiatric disorders before the birth, or the increase could be related to the burden of caring for their child. Aims: We aimed to calculate the incidence of a psychiatric diagnosis in women with no psychiatric history after the birth of their eldest child with autism spectrum disorder compared to women with no child with autism spectrum disorder o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…As we did [18,20], other research groups have demonstrated that mothers of children with ASD are more likely to have a psychiatric disorder [1,3,22] than other mothers. But only one research group had established an association with ID and maternal psychiatric disorders (severe ID only) [4].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…As we did [18,20], other research groups have demonstrated that mothers of children with ASD are more likely to have a psychiatric disorder [1,3,22] than other mothers. But only one research group had established an association with ID and maternal psychiatric disorders (severe ID only) [4].…”
Section: Discussionmentioning
confidence: 80%
“…Mothers with no psychiatric history and a child with ASD or ID were about twice as likely to have a new onset psychiatric disorder after the birth of their child than other mothers with no psychiatric history [20,21]. In these studies, we showed that mothers at highest odds of a psychiatric disorder were mothers of a child with ASD without ID, with nearly two and a half times the risk [20], followed by mothers of children with ID of unknown cause with more than one and a half times the risk (Figure 1) [21].…”
Section: Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of research has identified poorer health and QoL in the primary care-givers (here after referred to as care-givers) of children with ASD or ID than in other care-givers [5][6][7][8][9][10][11]. For example, using linked data, we demonstrated that in the years after their child's birth, mothers of children with ASD or ID had higher rates of psychiatric disorders than other mothers [9,10]. Furthermore, we also identified health differentials in mothers of children with different sub-types of ASD or ID [12].…”
Section: Introductionmentioning
confidence: 99%